UniMRI: Unified Repository of Magnetic Resonance Images for Multiple Sclerosis Diagnosis - Silveira, Wellington; Korb, Rafael; Dimuro, Graçaliz; Bem, Rodrigo de (Anais do Workshop de Visão Computacional (WVC); 2021: Anais do XVII Workshop de Visão Computacional, 2021)
Multiple sclerosis is an autoimmune disease that affects the central nervous system, destroying myelin. To detect multiple sclerosis, you need to have MRI scans so you can see the areas where myelin has been damaged. This analysis is complex and costly due to the time required to assess injuries. The use of machine learning is desirable as these exams are taken periodically. However, the number of public databases present in the literature containing patients with multiple sclerosis is small when compared to the amount of data needed to train deep neural networks. Thus, the objective of this work is to join public databases of magnetic resonance images existing in the literature, proposing a software library to manipulate and pre-process these data.